FORM SHIFTS IN TRANSLATING PASSIVE CLAUSES FOUND IN NOVEL HARRY POTTER: HARRY POTTER AND THE DEATHLY HALLOWS - Melyanda Agustin Chairina; Jufrizal Jufrizal; M Yusdi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
Shift is one of the phenomena in translation to suit with the acceptability of translation product. This article aims at finding out the shifts of form in translating passive clauses found in the novel Harry Potter translated by Listiana Srisanti. This research used a qualitative method where the research analysis relied on linguistic description and employed meaning-based to reveal and describe how is the existence of shifts of form and meaning in the translation. The data of this research were passive clauses taken from the novel “Harry Potter and the Deathly Hallows” as the source language (SL), and the passive clauses translation in the target language (TL) obtained from the translated Novel “Harry Potter dan Relikui Kematian.” Based on the data analysis, it shows that the translation shift of form comprised structure shifts 67 data (60%), class shifts 37 data (33 %), and unit shifts 8 data (7%). Even though the shifts found in the translation, there was an acceptable translation of passive clauses. Thus, it indicated that there are shifts in translation, but it was acceptable.